2012
DOI: 10.1089/ten.tea.2011.0285
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Loading of Stem Cells for Improvement of Transplantation Outcome in a Model of Acute Myocardial Infarction: The Role of Loading History

Abstract: Stem cell therapy for tissue repair is a rapidly evolving field and the factors that dictate the physiological responsiveness of stem cells remain under intense investigation. In this study we hypothesized that the mechanical loading history of muscle-derived stem cells (MDSCs) would significantly impact MDSC survival, host tissue angiogenesis, and myocardial function after MDSC transplantation into acutely infarcted myocardium. Mice with acute myocardial infarction by permanent left coronary artery ligation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Previous studies have shown a decrease in fibrosis and muscle necrosis with sustained VEGF secretion using gene or cell therapy40; however, when MS-MDSCs were transplanted into an infarcted heart they did not significantly affect fibrosis levels compared with the transplantation of NS-MDSCs 37. We examined collagen formation in muscles implanted with sFlt1-MDSCs, shRNA_VEGF-MDSCs, or lacZ-MDSCs and found increased fibrosis formation in all the groups where VEGF was blocked.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies have shown a decrease in fibrosis and muscle necrosis with sustained VEGF secretion using gene or cell therapy40; however, when MS-MDSCs were transplanted into an infarcted heart they did not significantly affect fibrosis levels compared with the transplantation of NS-MDSCs 37. We examined collagen formation in muscles implanted with sFlt1-MDSCs, shRNA_VEGF-MDSCs, or lacZ-MDSCs and found increased fibrosis formation in all the groups where VEGF was blocked.…”
Section: Discussionmentioning
confidence: 87%
“…Mechanical stretch is a powerful stimulus for a broad spectrum of cellular responses, including growth, differentiation, motility, remodeling, and gene expression 29,35,36. Previous studies demonstrated that mechanically stimulated MDSCs expressed more VEGF and were able to repair the infarcted hearts of mice more effectively than nonmechanically stimulated MDSCs,37 which was attributed, at least in part, to an increase in angiogenesis in the peri-infarct area 37. In addition, blocking VEGF with sFlt1-MDSCs abrogated the benefits of MDSCs in both skeletal muscle regeneration and cardiac repair 21,22…”
Section: Discussionmentioning
confidence: 99%
“…We have investigated whether in vitro mechanical stimulation has a beneficial effect on improving the transplantation capacity of MDSCs in cardiac muscle 47 52. We cultured MDSCs on flexible collagen-coated culture plates (Flexcell Intl Corp, Hillsborough, NC, USA).…”
Section: Introductionmentioning
confidence: 99%
“…At 2 weeks after cell implantation, the mice were sacrificed, and their hearts were harvested and stained for dystrophin expression. Infarcted hearts transplanted with stimulated MDSCs showed improved cardiac contractility, increased angiogenesis and decreased fibrosis compared with the hearts treated with non-stimulated MDSCs 52. Dystrophin-positive cells were counted for the largest engraftment area.…”
Section: Introductionmentioning
confidence: 99%
“…They can also focus on coaxing immature cells toward more complex morphologies. Furthermore, these cellular preconditioning approaches can also be based on electrical [33] or mechanical stimuli [34]. Ideally, upon exposure to these preconditioning routines, cells will express phenotypes mirroring those in the native tissue, and will remodel the ECM to reproduce the complicated morphology of the tissue being replaced.…”
Section: Tissue Engineeringmentioning
confidence: 99%